EFEKTIVITAS PEMANFAATAN ALOKASI DANA KAMPUNG (ADK) DALAM MENINGKATKAN PEMBANGUNAN EKONOMI DI KAMPUNG BUKIT MAKMUR, KABUPATEN BERAU: EFEKTIVITAS PEMANFAATAN ALOKASI DANA KAMPUNG (ADK) DALAM MENINGKATKAN PEMBANGUNAN EKONOMI DI KAMPUNG BUKIT MAKMUR, KABUPATEN BERAU - Agus Imam (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
This research aims to determine the level of effectiveness of the use of Village Fund Allocations (ADK) in increasing economic development in Bukit Makmur Village, Berau Regency. This research uses descriptive analysis methods. The data obtained in this study is primary data through interviews and filling out questionnaires. The tests carried out were validity, reliability and policy gap analysis. Policy gap analysis is used to assess government performance in terms of public policy/services by comparing plan input and factual implementation. The utilization of research village funds is seen in the dimensions of planning, implementation, evaluation and transparency. Based on the results of this research, no difference was found between expected service by the community and perceived service from the village government, where the difference value was 0.1171. Overall, this research used the independent t-test and obtained Sig. (2-tailed) of 0.424. These results show that there is a not very significant difference in the perception of the performance provided by the village government to the community regarding the effectiveness of village funds in supporting the economic development of Bukit Makmur village in 2021